The Effect of Cavity Shape and Hybrid Layer on the Stress Distribution of Cervical Composite Restorations - Eliguzeloglu, Evrim; Eraslan, Oguz; Omurlu, Huma; Eskitascioglu, Gurcan; Belli, Sema (European Journal of Dentistry, 2011)
Objectives: The aim of this finite elemental stress analysis study was to evaluate the effect of cavity shape and hybrid layer on the stress distribution of the mandibular premolar tooth under occlusal loading. Methods: The mandibular premolar tooth was selected as the model based on the anatomical measurements suggested by Wheeler. Four different mathematical models were evaluated: 1) a saucer-shaped non-carious cervical lesion restored with a composite without a hybrid layer, 2) a saucer-shaped non-carious cervical lesion restored with a composite with a hybrid layer, 3) a wedge-shaped non-carious cervical lesion restored with a composite without a hybrid layer, and 4) a wedge-shaped non-carious cervical lesion restored with a composite with a hybrid layer. A 200 N force was applied from the buccal tubercule and central fossa of the premolar tooth. The findings were drawn by the SAPLOT program. Results: In models 2 and 4, the output showed that a hybrid layer acts as a stress absorber. Additionally, when the cavity shape was changed, the stress distribution was very different. Conclusions: Cavity shape and hybrid layer play an important role in stress distribution in cervical restorations. (Eur J Dent 2011;5:180-185)
Keywords: Non-carious cervical lesion; Hybrid layer; Stress distribution; Finite element analysis; Premolar tooth